Size distribution and total number concentration of ultrafine and accumulation mode particles and hospital admissions in children and the elderly in Copenhagen, Denmark. Issue 7 (7th November 2007) - Andersen, Z J; Wahlin, P; Raaschou-Nielsen, O; Ketzel, M; Scheike, T; Loft, S
Abstract : Objectives: To study the association between short-term exposure to ultrafine particles and morbidity in Copenhagen, Denmark. Methods: We studied the association between urban background levels of the total number concentration of particles (NCtot, 6–700 nm in diameter) measured at a single site (15 May 2001 to 31 December 2004) and hospital admissions due to cardiovascular (CVD) and respiratory disease (RD) in the elderly (age ⩾65 years), and due to asthma in children (age 5–18 years). We examined these associations in the presence of PM10, PM2.5 (particulate matter <10 and 2.5 µm in diameter, respectively) and ambient gasses. We utilised data on size distribution to calculate NCtot for four modes with median diameters 12, 23, 57 and 212 nm, and NC100 (number concentration of particles <100 nm in diameter) and examined their associations with health outcomes. We used a time series Poisson generalised additive model adjusted for overdispersion, season, day of the week, public holidays, school holidays, influenza, pollen and meteorology, with up to 5 days' lagged exposure. Results and conclusions: The adverse health effects of particulate matter on CVD and RD hospital admissions in the elderly were mainly mediated by PM10 and accumulation mode particles with lack of effects for NC100 . For paediatric asthma, accumulation mode particles, NC100 and nitrogen oxides (mainly from traffic related sources) were relevant, whereas PM10 appeared to have little effect. Our results suggest that particle volume/mass from long-range transported air pollution is relevant for CVD and RD admissions in the elderly, and possibly particle numbers from traffic sources for paediatric asthma.